Crescimento e produção de primeiro ciclo da bananeira (Musa spp.) 'Prata anã' (aab) em sete espaçamentos, em Visconde do Rio Branco, MG - PEREIRA, MARLON CRISTIAN TOLEDO; SALOMÃO, LUIZ CARLOS CHAMHUM; SILVA, SEBASTÃO DE OLIVEIRA E; SEDIYAMA, CARLOS SIGUEYUKI; NETO, SEBASTIÃO PEDRO DA SILVA; COUTO, FLÁVIO ALENCAR D'ARAÚJO (Revista Ceres, 2015)
.